2018
DOI: 10.1080/17518253.2018.1511833
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots-enhanced luminol chemiluminescence and its application to 2-methoxyestradiol determination

Abstract: In this study, the fluorescent carbon dots (CDs) of good biocompatibility and low toxicity was prepared by a carbonation route, and a strong enhancement effect of CDs on the luminol-K 3 Fe (CN) 6 chemiluminescence (CL) system was observed. 5 ± 1 nm CDs were used as catalysts to enhance the reaction sensitivity. In the presence of 2-methoxyestradiol (2-ME), the CL intensity of CDs-luminol-K 3 Fe(CN) 6 was significantly inhibited. The relative CL intensity was linearly related to the 2-ME concentration in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to them, C-dots acted as a catalyst in the generation of oxygen related radicals that can accelerate the luminol oxidation which may lead to the production of more intermediate, 3-aminophthalate * and thereby increased the intensity of CL emission peak. The phenolic hydroxyl group in 2-ME reacted with K 3 Fe(CN) 6 , reduced the generation of intermediate, 3-aminophthalate * and hence obtained submissive CL intensity [143]. The same system was also used for the determination of gallic acid in food samples.…”
Section: Electrochemiluminescencementioning
confidence: 99%
“…According to them, C-dots acted as a catalyst in the generation of oxygen related radicals that can accelerate the luminol oxidation which may lead to the production of more intermediate, 3-aminophthalate * and thereby increased the intensity of CL emission peak. The phenolic hydroxyl group in 2-ME reacted with K 3 Fe(CN) 6 , reduced the generation of intermediate, 3-aminophthalate * and hence obtained submissive CL intensity [143]. The same system was also used for the determination of gallic acid in food samples.…”
Section: Electrochemiluminescencementioning
confidence: 99%
“…[3 -5] Catalysts and co-factors can reduce the activation energy of this reaction. [2,[6][7][8][9] In special cases, the irradiation of a fluorescent dye may trigger the light emission from a CL-reagent such as luminol (photo-induced CL). [10] Also, the transfer of energy from an excited species to a fluorophore that in turn gets excited and relaxes to its ground state by emitting a photon may occur (sensitized or indirect CL).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang et al reported an enhancement of CL intensity for the luminol-K 3 Fe(CN) 6 system when in the presence of CDs at alkaline pH. The as-fabricated CD composite material is used for the detection of anticancer drug 2methoxyestradiol (Figure 13(b))[57].…”
mentioning
confidence: 99%
“…(a) Mechanism for CL generated from CDs (b) enhance CL intensities diagram for (1) luminol-K 3 Fe(CN) 6 , (2) CDs-luminol-K 3 Fe(CN) 6 , and (3) CDs-luminol-K 3 Fe(CN) 6 -2-methoxyestradiol (reproduced with permission from[56,57]). Tuning of QY for CDs (i) PL spectrum of quantum dots having carboxylic acid as functionality (red line) and (ii) having hydroxyl functionality (blue line) (reproduced with permission from[61]).…”
mentioning
confidence: 99%